Untersuchungen über die Schädelvariabilität des Wildschweines, Sus scrofa L. aus Nordostpolen; Badania nad zmiennością czaszki dzika, Sus scrofa L. z północno-wschodniej Polski - Caboń, K. (1958)
Autorka zbadała 93 czaszki dzików z Białowieskiego Parku Narodowego i sąsiadujących nadleśnictw. Opisano rozwój i wzrost czaszki, szeroki wachlarz zmienności wymiarów czaszki i jej wskaźników ze zwróceniem uwagi na dymorfizm płciowy. Autorka stwierdza, że dziki białowieskie należą do dużych form Sus scrofa L. i mogą być zaliczone do podgatunku Sus scrofa atilla Thomas. Autorka przypuszcza, że do tej samej grupy zaliczyć należy dziki z terenów Polski w ogóle, oraz dziki wschodnioniemieckie. Acta Theriologica 2 (): 107-140, 1958
Keywords: Białowieża forest; North-east Poland; Polska; skull variability; Sus scrofa

Functional polarization of Poland’s North-Eastern small towns in the light of R. Camagni’s concept of territorial competitiveness - Korcelli-Olejniczak, Ewa. Autor; Piotrowski, Filip. Autor; Melnyk, Maryana. Autor (IGiPZ PAN, 2022)
Small towns’ functions are exposed to pressure stemming from globalization and metropolitan development. In North-East Poland, the study area, they are at the same time affected by the restructuring of rural economy. As in other peripheral regions in Europe, they are subject to de-population trends. The analysis of socioeconomic functions performed by small towns reveals functional polarization – a division line between local service centers and those towns additionally performing specialized functions. Whereas some towns succeed in sustaining, or attracting, often niche type industrial and service activities, others remain to rely upon the provision of private and public services for the surrounding rural places. By referring to R. Camagni’s conceptualization of territorial competitiveness, the role of selected territorial capital components – local entrepreneurship, social capital and local leadership is identified in the observed development of socio-economic functions of supra-local market range. The findings reveal the focusing, by the successful local firms upon the specificity of market offer, its linking with local tradition, skills, and natural resources. On the conceptual side, at a town level, they indicate the importance of mutual interlocking of individual endogenous factors in the development and the sustenance of competitive functions.
24 cm
Keywords: małe miasta; funkcje wyspecjalizowane; konkurencja terytorialna; region peryferyjny; Polska Północno-Wschodnia